Bubble Mediated Surface Modification in the Copper Electropolishing System - Pauric, Allen D. (My University, 2012)
Electropolishing is a commonly used method of mitigating surface roughness and yielding a polished appearance. One of the first described and most studied of electropolishing systems is the anodization of copper in phosphoric acid. Under normal conditions this reduces copper surface roughness substantially; however deviating from optimal electropolishing conditions can promote the development of semi-ordered surface roughness. Anodizing copper substrates in 98-100% H3PO4 solutions generated feature heights ranging from 0.5 - 2µm and surface area increases in excess of 30% were obtained. The samples demonstrated a macroscopic optical dullness characteristic of this type of surface roughening. Investigations as to their applicability in surface enhanced Raman spectroscopy and electron field emission were conducted. And while their formation mechanism is still speculated on, it is believed that oxygen evolution and subsequent bubble formation plays a key role. Electrochemical and microscopic imaging techniques were the primary methodologies used to probe the optical dulling phenomenon. With data obtained from experiments utilizing these techniques and others a qualitative mechanism is proposed.
Keywords: copper; electropolishing; oxygen evolution; bubbles; surface roughening; phosphoric acid; Physical Chemistry; Physical Chemistry